2020
DOI: 10.1016/j.jhep.2019.09.029
|View full text |Cite
|
Sign up to set email alerts
|

The Candida albicans exotoxin candidalysin promotes alcohol-associated liver disease

Abstract: Background & Aims: Alcohol-associated liver disease is a leading indication for liver transplantation and a leading cause of mortality. Alterations to the gut microbiota contribute to the pathogenesis of alcohol-associated liver disease. Patients with alcohol-associated liver disease have increased proportions of Candida spp. in the fecal mycobiome, yet little is known about the effect of intestinal Candida on the disease. Herein, we evaluated the contributions of Candida albicans and its exotoxin candidalysin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 35 publications
2
119
0
Order By: Relevance
“…In the setting of alcoholic liver diseases, overgrowth of Candida and the decrease of fungal diversity were found in the patients with different phases of liver diseases covering non-progressive alcoholic liver diseases, alcoholic hepatitis, and alcoholic cirrhosis. 11,27 In this study, we observed an overgrowth of fungi in the gut of mice with chronic ethanol feeding and further isolated a strain of M. guilliermondii that was enriched in the feces of ethanol-fed mice. By using a fungi-free mice model, we confirmed that the enrichment of M. guilliermondii in gut aggravated the fatty accumulation and inflammatory damages in liver of the ethanol diet-fed mice.…”
Section: Discussionmentioning
confidence: 82%
“…In the setting of alcoholic liver diseases, overgrowth of Candida and the decrease of fungal diversity were found in the patients with different phases of liver diseases covering non-progressive alcoholic liver diseases, alcoholic hepatitis, and alcoholic cirrhosis. 11,27 In this study, we observed an overgrowth of fungi in the gut of mice with chronic ethanol feeding and further isolated a strain of M. guilliermondii that was enriched in the feces of ethanol-fed mice. By using a fungi-free mice model, we confirmed that the enrichment of M. guilliermondii in gut aggravated the fatty accumulation and inflammatory damages in liver of the ethanol diet-fed mice.…”
Section: Discussionmentioning
confidence: 82%
“…This inhibitory effect is consistent with its major content in total phenolic compounds [24,25], as confirmed by both colorimetric assays (Table 1) and independent HPLC-fluorimetric analysis ( Table 7). While considering both the incidence of C. albicans opportunistic infections occurring in liver disorders [50] and the traditional use of Bridelia genus [9], a pharmacological investigation was subsequently performed to explore anti-proliferative effects against the liver cancer HepG2 cell line and protective effects on isolated rat liver specimens challenged with the LPS pro-inflammatory stimulus. The HepG2 cell viability was evaluated through the MTT test, which revealed a stimulatory effect induced by methanol extract, up to 48 hours following treatment (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It also correlates with a higher level of serum endotoxin and increased intestinal tumor necrosis factor‐α levels, as well as increased levels of nitric oxide, IL‐6, and IL‐8 . Another recent discovery is that patients with ALD not only have bacterial dysbiosis, but also show reduced fungal diversity, as well as Candida overgrowth . Indeed, using antifungal agents in mouse models has been shown to decrease β­glucan translocation and ameliorate alcohol­induced liver injury produced through the C­type lectin domain family 7 member A receptor on hepatic Kupffer cells .…”
Section: Introductionmentioning
confidence: 99%